Motivational orientations for participation in professional development programmes among secondary school principals in Sarawak - Matu Lejau, Marcus Hugo (2000)
Principals' competence is crucial in ensuring successful secondary schools in Sarawak. Therefore, it is important to understand the motivational orientations for participation in professional development programmes among principals and the motivational orientation factors, which influence the principals' participation in professional development programmes that are conducted by the Education Authorities. This study aims to determine the motivational orientations for participation in professional development programmes among principals in Sarawak and the motivational orientation factors that influence their participation.